Magnesium-catalyzed stereoselective transformations – A survey through recent achievements - Czombik, Anna M.; Gajewy, Jadwiga; Czapik, Agnieszka; Kwit, Marcin (Elsevier, 2022)
Magnesium (Mg) constitutes one of the most abundant metal elements in the Earth’s crust. The spectacular career of magnesium in organic chemistry has been initiated at the beginning of XX century and has still been lasting today. The discovery of organomagnesium compounds by Philippe A. Barbier and Victor Grignard is commonly recognized as one of the milestones in development of (organic) chemistry. The subsequent applications of Grignard reagents as relatively easy generated synthons in enantioselective reactions have opened new possibilities for acquiring enantiomerically enriched compounds. On the other hand, asymmetric reactions in which magnesium plays a role of catalyst can be considered still limited, especially when their number is compared to the number of contributions aimed at transition metal-catalyzed or organocatalyzed stereoselective trans formations. However, taking into account the current trends of replacing expensive metals with their cheaper counterparts and making catalysis more environmentally (and user) friendly, the development of new and modification of known methods, which employ Earth-abundant metals, is very advisable. In this study we intend to emphasize the role of magnesium in organic chemistry, mainly in catalytic asymmetric synthesis. Among the already reported catalytic procedures, we have discussed the most recent examples, however, we also mentioned some, the groundbreaking previous ones. An exception for the pericyclic reactions has been made, as these re actions constitute the first examples of the use of magnesium catalysis in asymmetric synthesis. An attention has been drawn to some structural aspects, associated with either experimentally-determined geometry of the cat alytic species or the calculated transition state(s) for a given asymmetric transformation.
Keywords: Magnesium; Asymmetric synthesis; Crystal structure; Chirality